Teaching Central Tendency Meaningfully: A Context-Based Trajectory using Water pH Levels - Retta, Allen Marga; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Susanti, Ely (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This study aims to design a contextual learning trajectory using water pH as an anchor to help student’s understand central tendency concepts, including mean, median, and mode. The research employed a design research approach within a qualitative descriptive framework, consisting of three main stages: preliminary design, design experiment, and retrospective analysis. In the preliminary design stage, a Hypothetical Learning Trajectory (HLT) was developed and aligned with the learning objectives, ensuring that the tasks were suitable for fostering students' understanding of the central tendency concepts. The design experiment involved data collection from a pilot experiment with 6 students and teaching experiment with 29 eighth-grade students at the junior high school. Data was gathered using instruments, including student worksheets, video recordings, field notes, and test. The data collected from students’ responses were analyzed to assess their understanding of the concepts. In the retrospective analysis stage, the Actual Learning Trajectory (ALT) was compared with the predicted HLT to identify any discrepancies and assess the effectiveness of the learning activities. The results showed that integrating the PMRI approach with Project-Based Learning (PjBL) successfully engaged students and contributed to their conceptual development, reinforcing the importance of using contextual problems such as water pH in teaching statistical concepts.